THE SCIENTIFIC HERITAGE OF IMAM ISО TERMIZI (TAMADDUN NURI JURNALI, 2024)
This article analyzes the scientific legacy of Imam Isa Tirmidhi and his contribution to the science of hadith studies based on historical sources.